Proximate and Fatty Acid Composition in Muscle Tissues of Rainbow Trout, Oncorhynchus Mykiss, Cultured in Yazd Province of Iran - MASHAII, Nassrin; MOSADDEGH, Mohammad Hossein; SARSANGI, Habib; RAJABIPOUR, Farhad; GHORGHI, Ahmad; BITARAF, Ahmad; MOZAFFARI-KHOSRAVI, Hassan (Walailak Journal of Science and Technology (WJST), 2012)
Iran is the number one producer of cultured coldwater fish in Asia since 2005. Rainbow trout, (Oncorhynchus mykiss) is the most common and important fish produced by Iranian fisheries. There is not enough information about carcass composition of cultured fish in Iran. Rainbow trout muscle samples were collected from six fish farms of Yazd province during February 2008. Muscle samples were frozen at -30 οC after being homogenized. Proximate composition of samples was measured. Saturated fatty acids including palmitic, stearic, myristic, lauric acids, also unsaturated fatty acids oleic and linoleic were extracted from muscle tissue of fish at different farms, using gas chromatograghy (GC). Other unsaturated fatty acids including α-linolenic acid, Eicosa Pentaenoic Acid (EPA) and Docosa Hexaenoic Acid (DHA) had low concentrations (up to 3 %) in samples. Vitamin E levels were 4.33 - 94.34 μg/100 g.